2013
DOI: 10.1111/trf.12481
|View full text |Cite
|
Sign up to set email alerts
|

Storage time affects umbilical cord blood viability

Abstract: This study demonstrates that extended precryopreservation storage adversely affects viability and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Importantly, the first cautious attempts to expand one of the grafts before dCB transplantation have significantly reduced the time to neutrophil recovery [25][26][27][28]32], although platelet recovery has remained substantially delayed when compared to current rather than historical transplant outcomes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the first cautious attempts to expand one of the grafts before dCB transplantation have significantly reduced the time to neutrophil recovery [25][26][27][28]32], although platelet recovery has remained substantially delayed when compared to current rather than historical transplant outcomes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Delays in cryopreservation after the collection of cells may adversely affect cell viability [61]. A study by Gutt­ridge et al [61] found that pre-cryopreservation storage time significantly affected the viability of CD34+ cells from UCB after cryopreservation, suggesting that extended pre-cryopreservation should be avoided.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…A study by Gutt­ridge et al [61] found that pre-cryopreservation storage time significantly affected the viability of CD34+ cells from UCB after cryopreservation, suggesting that extended pre-cryopreservation should be avoided. This finding is consistent with results of another study by Schwandt et al [62], which showed that the highest viability for cord blood cells was obtained when cells were cryopreserved directly after collection.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…According to these studies, the extending of the time from collection to processing determined a decrease in cell viability mainly for granulocyte, while the viability of CD34 + cells seems to not to be affected [7,21,22,28,34]. Thus, interested in knowing if a larger number of CD34 + cells ensure maintaining a higher cell viability, we noticed that there was a very reduced positive correlation (r = 0.0782; P < 0.0001) between these parameters.…”
Section: Tablementioning
confidence: 80%